A review of the Metalliferous Mineralization of the Lower Paleozoic Fiambalá Mafic-Ultramafic Complex, Argentina - Villar, Luisa Maria (2019)
The Cr+Ni+Co+PGE elements occurring at the Sierra de Fiambalá, Argentina (ca. 27º 49’ S - 67º 30’ W) are known to be genetically related to a Lower Paleozoic layered Ma c-Ultramafic (Fiambalá) Complex, where the mineralization is concentrated in the basal ultramafic layer formed by spinel dunites overlain by lherzolites, websterites and gabbronorites. The profiles of PGE fractionation of the Fiambalá lherzolites have the same characteristic signature –PGE concentrated in the sulfurized phase, with enrichment in Pt and Pd– of other layered mafic-ultramafic complexes such us the Bushveld and Stillwater complexes, developed in extensional contexts. The latter context may seem to be inconsistent with the Fiambalá Complex representing the root of a magmatic arc, but the fact that the locus of this Lower Paleozoic magmatic arc is known to have undergone extensive rifting during the Neoproterozoic (possibly up to Cambrian times) allows the present authors to propose that the Fiambalá Mafic-Ultramafic Complex has some geochemical and metalliferous inheritance from the predecessor extensional regime, whereby fragments of pre-existing MORB basement may have been assimilated into the parental magma of the Fiambalá Complex, represented by a number of samples collected near the western margin of the Complex, in the vicinity of a postulated feeder dyke